A digital correlation receiver for the Mingantu Spectral Radioheliograph. (2019) - Liu, Fei; Yan, Yihua; Wang, Wei; Tan, Baolin; Chen, Linjie; Qu, Chunhui; Li, Jutao
Abstract: We have designed and developed the digital correlation receiver for Mingantu Spectral Radioheliograph (MUSER). The MUSER digital correlation receiver is implemented to sample, channelise, and correlate a 400 MHz wide solar radio signal of 40-antenna output from MUSER intermediate-frequency array and 60-antenna output from MUSER high-frequency array. The polyphase filter channeliser is used for wide-band channelisation and proved to be efficient to realise narrow-band filtering ( ${\sim}25$ MHz) in a high-speed digital signal-processing pipeline (sampling rate ${\sim}1$ Gsps). All modules of the digital correlation receiver are implemented on FPGA-based hardware and integrated via high-speed backplane, which makes a well-performed and economical correlator system for MUSER array. The future upgrade is also addressed including spectral resolution enhancement and radio-frequency-interference excision.